Vantagens e desvantagens da estrutura de holding na administração pública: um estudo de caso do Ministério da Defesa - Azeredo, Priscilla Guerreiro de (2012)
This study sought to identify advantages and disadvantages of holding structure in Public Administration from the Department of Defense. We conducted a case study and we use the theoretical frameworks that allow us to understand the structure of holding company and subsidiaries, private management, the public management and the difference between them. Twelve interviews were conducted in two stages. The first comprised those who acted and possessed considerable knowledge about holding, at the second, people who possess knowledge of the Department of Defense and Armed Forces. The responses from the interviews were analyzed drawing on what was presented in Theoretical Framework. Overall, respondents said the following advantages of the holding in the public administration: to facilitate greater integration and dialogue between the parties; to centralize power guiding the direction of the organization, to facilitate the performance and strategic vision, to foster governance, strengthen dialogue, thought together and systemic action, identifying greater bargaining power and political representation, generating greater efficiency because of the understanding between the parties and best use of resources, allow the translation of goals into policies, increasing the possibility of reducing inequalities when they think only in profit, and seek public benefit. Disadvantages cited were increasing problems in sharing between units, the increased possibility of clashes of different cultures, the possibility of each manager to come back to his unit when resources are limited, the largest evacuation in the discussion of important issues in subsidiary, opening for the occurrence of rework; possibility of delays in delivery of purchases, which are now centralized, greater exposure to politicization and political influence, inadequate mechanisms of control performance, limitations and management decisions for what is established by law ; existence of forces acting and negotiating policies, lack of civilian careers in certain areas by increasing their exposure, lack of policy and political interference shielding, training and structuring unsatisfactory.